Land suitability assessment for Lansium domesticum cultivation on agroforestry land using matching method and geographic information system - RAHMAWATY RAHMAWATY; SINTIKE FRASTIKA; ABDUL RAUF; RIDWANTI BATUBARA; FITRAH SYAWAL HARAHAP (Society for Indonesian Biodiversity, 2020)
Abstract. Rahmawaty, Frastika S, Rauf A, Batubara R, Harahap FS. 2020. Land suitability assessment for Lansium domesticum cultivation on agroforestry land using matching method and geographic information system. Biodiversitas 21: 3683-3690. Lansium domesticum is one of the multipurpose tree species (MPTS) and is commonly found on agroforestry lands in Sumatra. This study aimed to evaluate the actual land suitability classes for L. domesticum and to map the potential land suitability for the species using matching method and geographic information system (GIS). The study was conducted in Sei Bingai Sub-district, Langkat District, North Sumatra, Indonesia. A survey was conducted to collect soil samples based on land units. Land unit information was obtained by overlaying soil map, land-use map, and slope map. Land suitability was evaluated based on the matching method and GIS was used to map the distribution of land suitability. The results showed that both the actual and potential land suitability classes based on matching approach for L. domesticum were moderately suitable (S2) which accounted for 88.95% of total land and marginally suitable (S3) which accounted for 11.05%. Availability of water (wa), erosion hazard (eh), root-zone medium (rc), oxygen availability (oa), and nutrient retention (nr) were the dominant limiting factors in this area. The most difficult constraints to manage were root-zone medium and water availability. The results of this study suggest that the development of L. domesticum in Sei Bingai is possible although it requires some land improvements to deal with the limiting factors.